Activated Carbon From Mangrove By Microwave Irradiation For Adsorption Of Lead(Ii) Ions - Paul, Timothy Stephen Raj (Universiti Sains Malaysia, 2022)
Lead is a toxic heavy metal known as an environmental pollutant and the expansion of industries caused more effluents containing lead (II) ions are discharged to the water bodies. Adsorption approach was proposed using activated carbon derived from biomass due to ease in production, economical and ability to adsorb metal ions. The present research reports an activated carbon synthesized from mangrove via microwave heating in the presence of CO2 to remove Pb(II) ions. The production of mangrove-based AC using microwave heating is proposed due to availability of mangrove in Malaysia and significant reduction in activation time and energy consumption. Response Surface Methodology (RSM) is implemented to determine the optimal variables in producing the activated carbon from mangrove at optimum conditions whereby the optimum conditions were achieved at 616W and 6 mins. The AC that had been optimized was characterized using an FTIR and an elemental analyzer. Through the FTIR analysis the adsorption of Pb(II) ions to AC was mainly due to -OH stretch. From the elemental analysis, carbon was the major element found in the prepared activated carbon. Batch experiments were performed to examine the adsorption behavior of Pb(II) on the mangrove-based activated carbon. The highest removal was 75.68% recorded at AC dose of 0.4g with concentration of 10 mg/L, pH 6 and 30oC. The adsorption isotherm and kinetics studies showed that the adsorption followed Langmuir isotherm and PSO model respectively. The thermodynamic study suggested that the nature of the system was exothermic and spontaneous.